School Literacy Program Against Merdeka Thinking to Strengthen The Humanistic Learning Process at The Elementary School Level - Muhammadin, Ayatullah; Pamungkas, Sri (Berpusi Publishing, 2024)
This research aims to 1) Eliminate the uniform clothing system for students, 2) Implement a humanist learning system. The method used is literature review with a qualitative descriptive approach. Data collection techniques use interviews, observation and analysis of analyzed notes. The data taken are documents related to research. The research results show that learning is prioritized using a humanistic approach, but in reality there are still many learning processes that do not implement humanistic learning as a whole. For example, uniformity in clothing for students will ultimately kill students' potential, talents, interests, creativity and work results. The recommendation of this research is that a bottom-up curriculum model is worthy of being developed, so that educational components can strive for the overall curriculum components. However, an educator is a planner, implementer and perfectionist in a learning process. Because educators are the ones who best understand the conditions in the field from Sabang to Merauke, therefore educators are the most competent in compiling a curriculum in the classroom or at school. So the researchers recommend that the school literacy program